Effect of Variable Viscosity, Arrhenius Activation on Non-Darcy Convective Heat Transfer Flow of SWCNT And MWCNT in a Vertical Channel with Heat Sources - Y Madhusudhana Reddy (Mathematical Statistician and Engineering Applications, 2020)
In this paper, the combined influence of Arrhenius activation, on non-Darcy hydro magnetic convective heat and mass transfer of a nanofluid in vertical channel with SWCNT and MWCNT. The coupled nonlinear equations governing flow heat transfer have been analyzed by adopting Runge-Kutta fourth order with shooting technique. The effect of variable viscosity, activation energy, heat sources, chemical reaction on the flow characteristic have been studied graphically. The Skin friction, the rate of heat and mass transfer are numerically evaluated for different parametric variations. A rise in velocity and temperature and decay in concentration is noticed with rising values of variable viscosity (B), activation energy (E1) and a depreciation is noticed in them with higher values of temperature different parameter (d).